HYBRID DIGITAL-ADAPTIVE SUPERVISION FOR STRENGTHENING PROFESSIONAL KNOWLEDGE IN USE AND TEACHER PROFESSIONALISM IN THE ERA 5.0 - Rini Agustyowati; Achmad Supriyanto; Rochmawati (RADJA PUBLIKA, 2025)
This study aims to examine the effectiveness of integrating digital supervision and the adaptive approach to strengthening Professional Knowledge in Use (PKiU) and enhance teacher professionalism in junior high schools within the Society 5.0 era. A descriptive qualitative approach with a multi-site case study design was used. Data were collected through semi-structured interviews, observations, and document analysis, then analysed thematically to explore supervisory practices in three junior high schools. Integrated digital and adaptive supervision accelerates reflective practices, delivers personalized guidance, and fosters applicable PKiU development. Effectiveness depends on digital infrastructure, leadership, and culture, with challenges including digital literacy gaps and bureaucratic barriers. This study benefits educational management, teacher professional development, supervision policy design, and technology integration in schools, especially in contexts adopting Society 5.0 principles and digital transformation in education. The study introduces a hybrid supervision model combining digital tools with adaptive approach, providing a flexible, context-sensitive framework tailored to diverse teacher needs and digital literacy levels, advancing theory and practice in modern educational supervision.